Circulating tumor DNA detection (liquid biopsy): prospects in oncology - N. V. Zhukov; A. R. Zaretskiy; S. A. Lukyanov; S. A. Rumyantsev (Онкогематология)
Modern research techniques allows tumor studying in almost any level: protein expression, structural changes of DNA, RNA, epigenetic changes, activity of signaling pathways, microenvironment, interaction with the immune system, etc. However, tumor samples are obtained as 100 years ago – by tumor biopsy prior to treatment. Based on available data about intratumoral heterogeneity and tumor changes during treatment, it may be one of the factors braking to obtain required information of tumor biology. According to study, the analysis of circulating tumor DNA (ctDNA) allows to hope to overcome the key limitations of routine biopsy. One of the key benefits of ctDNA analysis is the ability to a more comprehensive tumor investigation, while maintaining a high level of specificity, almost as well as a routine biopsy. Detection sensitivity of ctDNA continues to increase due to the development of new technology. The study of ctDNA may lead to breakthrough results in understanding of tumors molecular heterogeneity, development of resistance to anticancer therapy and ways to overcome it, screening and a number of other key areas of modern oncology.